Mirror-surface low-light miliaria-free glaze as well as preparation method and application thereof

Through the specific formula of mirror low-light glaze-free glaze and optimized tile surface glaze preparation raw materials and processes, the orange-shaped appearance and crystallization problems caused by the differences in refractive index and reflectivity of the existing tile surface glaze are solved, achieving high The density, wear resistance and slip resistance improve the overall performance of ceramic tiles.

CN119306396AActive Publication Date: 2025-01-14GUANGDONG NEWPEARL CERAMIC GRP CO LTD +2

Patent Information

Application Number
CN202411491545.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-14
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

After melting at high temperature, the glaze on the surface of the existing ceramic tile is very different due to the large difference in refractive index and reflectivity, resulting in an orange-shaped appearance. The melting agent causes crystallization phenomenon, affecting the aesthetics, and lacks wear resistance and slip resistance, and conventional polishing The method can easily destroy the glaze layer structure of the brick surface, resulting in whitening and uneven texture.

Method used

Use specific formulas to mirror low-light glaze without prickly glaze, including potassium feldspar, sodium feldspar, calcined kaolin, barium carbonate, calcined zinc oxide, strontium carbonate, calcined talc, first fuse and second fuse to form a uniform material. The glass phase and columnar crystals improve the bonding density and wear resistance of the glaze surface. At the same time, by optimizing the preparation materials and processes of the surface glaze layer, the temperature difference between the blank and the surface glaze layer is reduced, and the porosity and light scattering rate are reduced, so as to achieve Low-light mirror effect and delicate texture.

Benefits of technology

It achieves flat glaze, low-light mirror effect, delicate texture, wear resistance and anti-slip properties, avoids appearance defects such as orange peel and prickly heat, and improves the comprehensive performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a mirror surface low-light miliaria-free glaze and a preparation method and application thereof, and belongs to the technical field of materials.According to the mirror surface low-light miliaria-free glaze, through selection of specific preparation raw materials, when the mirror surface low-light miliaria-free glaze is applied to a ceramic tile, the interlayer bonding performance of a product can be good, the bonding compactness of a glass phase and microcrystal particles on the glaze surface is high, and the service life of the product is prolonged. The glaze surface is flat, shows a low-light mirror surface effect, does not have appearance defects such as orange peel and prickly heat, is fine, smooth and mild in texture, and is good in wear resistance and slip resistance during application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a mirror-surface low-gloss, non-rash glaze and a preparation method and application thereof. Background Art

[0002] At present, mainstream ceramic tiles generally adjust the raw material formula of the surface glaze so that the surface glaze can obtain a suitable glass phase after high-temperature melting, or use conventional ceramic tiles for polishing to achieve a fine texture effect. However, the refractive index and reflectivity of some melts in conventional surface glazes are quite different for light, which makes the glaze surface have an orange peel-like appearance with a large drop. The fluxing agent often introduced into the surface glaze will cause crystallization, which will also cause a similar orange peel appearance effect, and even cause the glaze to be not tightly stacked during the firing process, resulting in defects similar to prickly heat, affecting the appearance of the product. Although the conventional polishing method will not cause the orange peel appearance, this processing method is very easy to destroy the glaze layer structure of the tile surface, and will cause the tile surface to appear white.

[0003] In addition, the existing fine-textured tiles generally have problems of unevenness and poor wear resistance, and their comprehensive use cost-effectiveness is not high. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a mirror-like low-gloss, non-prickly heat glaze. Through the selection of specific preparation raw materials, the product can have good interlayer bonding when applied to tiles, the glass phase and microcrystalline particles on the glaze surface are tightly bonded, the glaze surface is smooth and presents a low-gloss mirror effect, there are no appearance defects such as orange peel and prickly heat, the texture is delicate and warm, and at the same time, it has good wear resistance and anti-slip properties when used.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A mirror-like low-gloss, non-rash glaze comprises the following raw materials in parts by weight:

[0007] 15-25 parts of potassium feldspar, 10-15 parts of sodium feldspar, 8-15 parts of calcined kaolin, 2-5 parts of barium carbonate, 3-6 parts of calcined zinc oxide, 3-5 parts of strontium carbonate, 5-10 parts of calcined talc, 10-18 parts of the first frit, 10-20 parts of the second frit, 2-4 parts of corundum, and 2-5 parts of wollastonite.

[0008] The first frit includes the following chemical components in percentage by mass: Al2O3 16.58-18.94%, SiO2 56.34-60.65%, K2O 3.65-4.56%, Na2O 2.35-3.58%, CaO 15.62-17.50%, MgO 2.02-3.85%;

[0009] The second frit includes the following chemical components in percentage by mass: Al2O3 18.58-20.94%, SiO2 49.34-55.15%, K2O 0.65-1.06%, Na2O 2.85-4.58%, CaO 8.62-10.50%, BaO 8.19-10.54%, ZnO 2.86-4.45%, and MgO 3.15-4.45%.

[0010] In the technical solution of the present invention, in order to make the glaze surface have an orange peel appearance without crystallization and the refraction and reflection effects caused by large height difference, and at the same time achieve a delicate texture, potassium feldspar, sodium feldspar and quartz-type minerals are used as the main raw materials, so that the glass phase formed during the firing process can achieve a low and uniform light reflectivity, and achieve a low light effect. At the same time, two special compositions of frits are added for compounding. The raw materials will precipitate columnar calcium feldspar, barium feldspar, and zinc aluminum spinel crystals during firing. Such evenly distributed fine crystals will not produce microcracks due to the mismatch between the expansion coefficients of the crystals and the glass phase. The glaze surface has high wear resistance, and can also improve the fluidity of the glaze layer, effectively reduce the roughness of the glaze surface, and thus have a delicate feel. Moreover, due to the tight stacking, no prickly heat defects will be produced, so that the product has a mirror effect. On the other hand, the glaze layer formed by the two frits when fired at high temperature has a small porosity and a low light scattering rate, so it has good light transmittance, can effectively present the printed pattern of the brick surface, and has a good texture effect.

[0011] Preferably, the mirror-finished low-gloss, non-tarnished glaze comprises the following chemical components in percentage by mass: Al2O3 18.10-20.12%, SiO2 49.94-58.51%, K2O 3.11-4.05%, Na2O 1.89-3.05%, CaO 4.12-6.68%, MgO 3.02-4.85%, ZnO 3.16-5.25%, BaO 4.19-6.54%, and SrO 2.01-3.15.

[0012] Different preparation raw materials will form different glass phases and precipitate different types of crystals. If the glass phase is not selected properly and its intrinsic strength is low, then after firing and precipitating crystals, due to the difference in expansion coefficients, the glass phase is prone to microcracks under the extrusion of the crystals, which will not only lead to poor wear resistance of the product, but also cause defects such as apparent orange peel and prickly heat, resulting in a lack of mirror and low-light effects on the surface. In the glaze composition of the present invention, the glass phase formed by potassium, sodium and quartz phases has low reflectivity, small gloss drop, good flatness and appearance, fine texture, ideal mirror effect, and anti-slip properties. At the same time, it has a high aluminum oxide content, high hardness and good wear resistance.

[0013] Preferably, the mirror-finished low-gloss, non-prickly ash glaze comprises the following raw materials in parts by weight:

[0014] 20-25 parts of potassium feldspar, 10-15 parts of sodium feldspar, 12-14 parts of calcined kaolin, 3-4 parts of barium carbonate, 3-4 parts of calcined zinc oxide, 3.5-4.5 parts of strontium carbonate, 5-10 parts of calcined talc, 10-14 parts of the first frit, 15-19 parts of the second frit, 2-4 parts of corundum, and 2-3 parts of wollastonite;

[0015] The mirror-like low-gloss, non-embryo-resistant glaze comprises the following chemical components in percentage by mass: Al2O3 18.15-19.29%, SiO2 53.05-55.36%, K2O 3.49-3.68%, Na2O 2.03-2.66%, CaO 4.42-5.12%, MgO 3.15-4.35%, ZnO 3.62-4.60%, BaO 4.25-4.55%, and SrO 2.93-3.13%.

[0016] The mirror-like low-gloss, prickly-heat-free glaze obtained by using the raw materials and composition prepared in the present invention can maintain a glossiness of 12 to 16°, and at the same time has high flatness, no defects such as prickly heat, presents an ideal mirror effect, and has a fine texture. When the above-mentioned preferred formula ratio is adopted, the surface texture of the product can be further improved by controlling the glass phase component, the aluminum oxide tetrahedron ratio, and the key crystal forming raw materials, making the texture more delicate and the magnified microscopic effect better.

[0017] Another object of the present invention is to provide a ceramic tile, comprising the mirror surface low-gloss non-rash glaze of the present invention;

[0018] The ceramic tile comprises a body, a surface glaze layer, an inkjet printing layer, a protective glaze layer and a mirror-like low-gloss non-prickly heat glaze which are stacked in sequence;

[0019] The surface glaze layer comprises the following raw materials in parts by weight: 8-15 parts of calcined kaolin, 15-25 parts of potassium feldspar, 15-30 parts of sodium feldspar, 5-9 parts of wollastonite, 5-10 parts of a third frit, 3-5 parts of calcined zinc oxide, 5-10 parts of zirconium silicate, 5-12 parts of quartz, 7-12 parts of calcined aluminum oxide, and 5-10 parts of a fourth frit;

[0020] More preferably, the surface glaze layer comprises the following raw materials in parts by weight: 10-12 parts of calcined kaolin, 15-18 parts of potassium feldspar, 20-25 parts of sodium feldspar, 5-6 parts of wollastonite, 7-10 parts of the third frit, 3-4 parts of calcined zinc oxide, 8-10 parts of zirconium silicate, 8-10 parts of quartz, 7-10 parts of calcined alumina, and 5-10 parts of the fourth frit;

[0021] The third melt comprises the following chemical components in percentage by mass: Al2O3 17.65-19.45%, SiO2 52.24-56.68%, K2O 4.45-6.04%, Na2O 6.34-8.01%, CaO 8.12-12.18%, ZnO 1.01-2.45%;

[0022] The fourth melt includes the following chemical components in mass percentage: Al2O3 10.14-15.12%, SiO2 50.14-55.68%, K2O 4.15-5.04%, Na2O 1.04-1.85%, CaO 8.12-10.18%, ZnO 4.01-5.45%, BaO 10.56-13.16%, and B2O 3 1.98-3.54%.

[0023] In the existing products, there is a temperature difference between the body and the glaze when they are fired and combined. The excessive temperature difference is not only not conducive to the discharge of the gas generated during the firing process, but also causes a local violent reaction due to the excessive temperature difference, and finally causes a crack defect similar to prickly heat. Therefore, in the ceramic tile product described in the present invention, in addition to the use of mirror low-gloss prickly heat-free glaze, the inventor has also optimized and developed the surface glaze. On the one hand, the inventor introduced a type of raw material with a temperature difference close to that of the body material during firing, thereby reducing the temperature difference between the glaze and the body layer during the firing process, forming an exhaust space between the two, and at the same time introducing A calcium-sodium frit and a third and fourth frit containing BaO and B2O3 are added. The combination of the two can make the glaze present a certain matte effect after firing. At the same time, the network structure formed by the aluminum oxide tetrahedron formed by the aluminum source and the silicon oxide tetrahedron in the glass phase has high density, hard texture as a whole, good wear resistance, and high bonding strength with the body layer. If conventional glaze materials are used to prepare the glaze, not only may there be appearance problems, low gloss, and inability to form a low-light mirror effect, but there will also be prickly heat defects, and even wear resistance and texture will be affected by the glaze texture and interlayer bonding.

[0024] Preferably, the glaze layer includes the following chemical components in mass percentage: Al2O320.12-25.56%, SiO252.14-59.14%, K2O2.15-3.25%, Na2O2.85-4.51%, CaO3.05-5.18%, B2O30.34-0.51%, MgO0.22-1.05%, ZnO2.15-3.85%, BaO0.39-1.24%, ZrO24.54-7.65%.

[0025] More preferably, the glaze layer comprises the following chemical components in percentage by mass: Al2O3 20.33-23.23%, SiO2 55.14-58.14%, K2O 2.55-2.85%, Na2O 2.96-3.12%, CaO 3.72-4.23%, B2O 3 0.34-0.48%, MgO 0.29-0.44%, ZnO 3.36-3.59%, BaO 0.57-0.98%, ZrO 2 5.28-6.48%

[0026] Another object of the present invention is to provide a method for preparing the ceramic tile, comprising the following steps:

[0027] (1) providing a body layer, and then polishing the body layer;

[0028] (2) spraying water on the polished body layer to cool it down, and then providing a glaze layer on the body layer;

[0029] (3) Printing a pattern on the glaze layer to form an inkjet printing layer;

[0030] (4) providing a protective glaze layer on the inkjet printing layer;

[0031] (5) applying a mirror-like low-gloss, non-rash glaze on the protective glaze layer to obtain a rough blank;

[0032] (6) The rough blank is fired at 1180-1200° C., cooled, and edge-ground to obtain the ceramic tile.

[0033] Preferably, the raw material for preparing the protective glaze layer is the same as that for the mirror-finished low-gloss, non-tarnished glaze.

[0034] More preferably, the protective glaze layer is provided by electrostatically spraying a protective glaze slurry, wherein the protective glaze slurry comprises water and a raw material for preparing a mirror-like low-gloss non-prickly heat glaze, with a specific gravity of 1.18 to 1.28 g / mL and a glaze application amount of 105 to 135 g / m 2 .

[0035] More preferably, the mirror surface low gloss non-prickly heat glaze is set by spraying the mirror surface low gloss non-prickly heat glaze slurry, the mirror surface low gloss non-prickly heat glaze slurry comprises water and the preparation raw materials of the mirror surface low gloss non-prickly heat glaze, the specific gravity is 1.88-1.92 g / mL, the spraying flow rate is 33-38 s / 100 mL, and the glazing amount is 410-450 g / m 2 .

[0036] As described above, the raw materials for preparing the mirror low-gloss and prickly-heat-free glaze of the present invention can form a glaze layer with high density and low probability of forming microcracks during the firing process, and can effectively display the printed pattern. Diluting it into a glaze slurry for protective glaze and using it as a protective glaze can not only avoid prickly heat and orange peel-like defects on the glaze surface, but also form a gradient setting with the mirror low-gloss and prickly-heat-free glaze, which has better adaptability.

[0037] Preferably, the surface glaze layer is provided by spraying a glaze slurry, wherein the glaze slurry comprises water and raw materials for preparing the surface glaze layer, has a specific gravity of 1.88-1.92 g / mL, a spraying flow rate of 33-38 s / 100 mL, and a glaze application amount of 410-450 g / m 2 .

[0038] Preferably, the green body layer comprises the following raw materials in parts by weight: 12-20 parts of kaolin, 20-25 parts of potassium sodium sand, 15-20 parts of ball clay, 5-10 parts of bentonite, 20-25 parts of potassium sodium water-ground powder, 3-8 parts of calcined talc, and 2-5 parts of pyrophyllite.

[0039] It should be noted that the chemical composition of the mirror-finished low-gloss, non-rash glaze and the frit in its preparation raw materials, as well as the surface glaze layer and the frit in its preparation raw materials described in the present invention, in addition to the substances described above, also includes trace amounts of residual substances (such as impurities and loss on ignition), which are well known to those skilled in the art. Therefore, even without further detailed explanation, in the case where these substances themselves do not affect the physical properties and performance of the product, the scheme is complete and clear, and those skilled in the art will not believe that the scheme is limited due to the neglect of these components.

[0040] The beneficial effect of the present invention is that the present invention provides a mirror-like low-gloss, non-prickly heat glaze. Through the selection of specific preparation raw materials, when applied to ceramic tiles, the product can have good interlayer bonding, the glass phase and microcrystalline particles on the glaze surface are tightly bonded, the glaze surface is smooth and presents a low-gloss mirror effect, there are no appearance defects such as orange peel and prickly heat, the texture is delicate and warm, and at the same time, it has good wear resistance and anti-slip properties when used. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a schematic diagram of the brick surface of the ceramic tile described in Example 1 of the present invention.

[0042] Figure 2 This is a schematic diagram of the brick surface of the ceramic tile described in Comparative Example 4 of the present invention.

[0043] Figure 3 This is a schematic diagram of the brick surface of the ceramic tile described in Comparative Example 6 of the present invention.

[0044] Figure 4 This is a schematic diagram of the brick surface of the ceramic tile described in Comparative Example 1 of the present invention.

[0045] Figure 5 This is a schematic diagram of the brick surface of the ceramic tile described in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0046] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0047] Example 1

[0048] The present invention discloses a mirror surface low-gloss non-prickly heat glaze and a preparation method and application thereof. The mirror surface low-gloss non-prickly heat glaze is arranged on a tile. The preparation method of the tile is as follows:

[0049] (1) providing a green body layer, wherein the moisture content of the green body layer is less than 0.3% and the strength is 2 MPa, and then polishing the green body layer;

[0050] The green body layer comprises the following raw materials in parts by weight: 15 parts of kaolin, 25 parts of potassium sodium sand, 25 parts of ball clay, 7 parts of bentonite, 20 parts of potassium sodium water-ground powder, 5 parts of burnt talc, and 3 parts of pyrophyllite;

[0051] (2) Spray the polished body layer with 25g / m 2 The water is cooled to reduce the pore opening rate, and then a glaze layer is arranged on the body layer;

[0052] The surface glaze layer is set by spraying the surface glaze slurry, which includes the preparation raw materials of the surface glaze layer, 40wt% of water, 0.15wt% of sodium methyl cellulose, and 0.35wt% of sodium tripolyphosphate. After mixing, the glaze slurry is ball milled and sieved through 325 meshes, with a sieve residue of 0.6-0.8wt%. The specific gravity of the obtained glaze slurry is 1.9g / mL, the spraying flow rate is 35s / 100mL, and the glaze application amount is 420g / m 2 ;

[0053] The raw materials for preparing the surface glaze layer include the following components in parts by weight: 12 parts of calcined kaolin, 15 parts of potassium feldspar, 22 parts of sodium feldspar, 5 parts of wollastonite, 8 parts of the third frit, 3 parts of calcined zinc oxide, 10 parts of zirconium silicate, 10 parts of quartz, 10 parts of calcined aluminum oxide, and 5 parts of the fourth frit;

[0054] The third frit includes the following chemical components in percentage by mass: Al2O3 18.61%, SiO2 55.23%, K2O 4.85%, Na2O 7.38%, CaO 11.81, ZnO 1.25;

[0055] The fourth frit includes the following chemical components in percentage by mass: Al2O3 10.22%, SiO2 50.90%, K2O 4.70%, Na2O 1.22%, CaO 10.11%, ZnO 4.79%, BaO 13.16%, B2O 3 2.92%;

[0056] (3) Printing a pattern on the glaze layer to form an inkjet printing layer;

[0057] (4) providing a protective glaze layer on the inkjet printing layer;

[0058] (5) applying a mirror-like low-gloss, non-rash glaze on the protective glaze layer to obtain a rough blank;

[0059] When setting the protective glaze layer and the mirror low-gloss and prickly-heat glaze, the protective glaze layer is sprayed with the protective glaze slurry through an electrostatic glaze spraying cabinet, and the mirror low-gloss and prickly-heat glaze is set by spraying the mirror low-gloss and prickly-heat glaze slurry. The mirror low-gloss and prickly-heat glaze slurry includes the preparation raw materials of the mirror low-gloss and prickly-heat glaze, and also includes 40wt% of water, 0.15wt% of sodium methyl cellulose, and 0.35wt% of sodium tripolyphosphate. After mixing, the glaze slurry is also ball-milled and sieved through 325 meshes, with a sieve residue of 0.6-0.8wt%. The obtained glaze slurry has a specific gravity of 1.9g / mL, a spray flow rate of 35s / 100mL, and a glazing amount of 420g / m 2 ;

[0060] The raw materials for preparing the mirror surface low-gloss non-prickly heat glaze include the following components in parts by weight: 20 parts of potassium feldspar, 12 parts of sodium feldspar, 12 parts of calcined kaolin, 3 parts of barium carbonate, 4 parts of calcined zinc oxide, 4 parts of strontium carbonate, 10 parts of calcined talc, 12 parts of the first frit, 18 parts of the second frit, 2 parts of corundum (325 mesh), and 3 parts of wollastonite;

[0061] The first frit includes the following chemical components in percentage by mass: Al2O3 17.13%, SiO2 56.46%, K2O 4.03%, Na2O 3.05%, CaO 16.02%, MgO 2.27%;

[0062] The second frit includes the following chemical components in percentage by mass: Al2O3 19.29%, SiO2 49.83%, K2O 0.83%, Na2O 3.54%, CaO 8.85%, BaO 9.32%, ZnO 3.61%, and MgO 3.19%.

[0063] The glaze slurry for the protective glaze layer is a glaze slurry obtained by further diluting the mirror low-gloss non-prickly ash glaze slurry with water. The specific gravity of the glaze slurry is 1.18 g / mL, and the glaze application amount is 105 g / m 2 .

[0064] (6) The rough blank is fired at 1186° C. for 40 min, cooled, and edge-ground to obtain the ceramic tile.

[0065] Example 2

[0066] The embodiment of the mirror-like low-gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 1 only in that the raw materials for preparing the surface glaze layer include the following components in parts by weight:

[0067] 10 parts of calcined kaolin, 18 parts of potassium feldspar, 20 parts of sodium feldspar, 6 parts of wollastonite, 7 parts of the third frit, 3 parts of calcined zinc oxide, 8 parts of zirconium silicate, 10 parts of quartz, 8 parts of calcined alumina, and 10 parts of the fourth frit.

[0068] Example 3

[0069] The embodiment of the mirror-like low-gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 1 only in that the raw materials for preparing the surface glaze layer include the following components in parts by weight:

[0070] 15 parts of calcined kaolin, 15 parts of potassium feldspar, 25 parts of sodium feldspar, 6 parts of wollastonite, 10 parts of the third frit, 3 parts of calcined zinc oxide, 8 parts of zirconium silicate, 8 parts of quartz, 7 parts of calcined alumina, and 5 parts of the fourth frit.

[0071] Example 4

[0072] The embodiment of the mirror surface low gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 1 only in that the raw materials for preparing the mirror surface low gloss non-prickly heat glaze include the following components in parts by weight:

[0073] 25 parts of potassium feldspar, 10 parts of sodium feldspar, 14 parts of calcined kaolin, 3 parts of barium carbonate, 4 parts of calcined zinc oxide, 3 parts of strontium carbonate, 6 parts of calcined talc, 14 parts of the first frit, 15 parts of the second frit, 2 parts of corundum (325 mesh), and 3 parts of wollastonite.

[0074] Example 5

[0075] The embodiment of the mirror surface low gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 1 only in that the raw materials for preparing the mirror surface low gloss non-prickly heat glaze include the following components in parts by weight:

[0076] 25 parts of potassium feldspar, 15 parts of sodium feldspar, 12 parts of calcined kaolin, 3 parts of barium carbonate, 3 parts of calcined zinc oxide, 3 parts of strontium carbonate, 5 parts of calcined talc, 12 parts of the first frit, 15 parts of the second frit, 3 parts of corundum (325 mesh), and 2 parts of wollastonite.

[0077] Example 6

[0078] The embodiment of the mirror-like low-gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 2 only in that:

[0079] The raw materials for preparing the mirror surface low-gloss non-rash glaze include the following components in parts by weight:

[0080] 25 parts of potassium feldspar, 10 parts of sodium feldspar, 14 parts of calcined kaolin, 3 parts of barium carbonate, 4 parts of calcined zinc oxide, 4 parts of strontium carbonate, 6 parts of calcined talc, 14 parts of the first frit, 15 parts of the second frit, 2 parts of corundum (325 mesh), and 3 parts of wollastonite.

[0081] Example 7

[0082] The embodiment of the mirror-like low-gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 2 only in that the glaze slurry glazing amount of the surface glaze layer is 430g / m 2 The glaze amount of the mirror low-gloss non-prickly heat glaze is 430g / m 2 .

[0083] Example 8

[0084] The embodiment of the mirror-like low-gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 1 only in that the glaze slurry glazing amount of the surface glaze layer is 450g / m 2 The glaze amount of the mirror low-gloss non-prickly heat glaze is 450g / m 2 .

[0085] Example 9

[0086] The embodiment of the mirror-like low-gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from the embodiment 1 only in that the raw materials for preparing the surface glaze layer include the following components in parts by weight: 12 parts of calcined kaolin, 18 parts of potassium feldspar, 20 parts of sodium feldspar, 5 parts of wollastonite, 8 parts of the third frit, 3 parts of calcined zinc oxide, 7 parts of zirconium silicate, 12 parts of quartz, 10 parts of calcined aluminum oxide, and 5 parts of the fourth frit;

[0087] Example 10

[0088] The embodiment of the mirror-finished low-gloss, non-prickly ash glaze and its preparation method and application described in the present invention is different from Example 1 only in that the raw materials for preparing the surface glaze layer include the following components in parts by weight: 15 parts of calcined kaolin, 15 parts of potassium feldspar, 22 parts of sodium feldspar, 5 parts of wollastonite, 8 parts of the third frit, 3 parts of calcined zinc oxide, 10 parts of zirconium silicate, 8 parts of quartz, 9 parts of calcined aluminum oxide, and 5 parts of the fourth frit.

[0089] Embodiment 11

[0090] The embodiment of the mirror-surface low-gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from Example 1 only in that the raw materials for preparing the mirror-surface low-gloss non-prickly heat glaze include the following components in parts by weight: 20 parts of potassium feldspar, 14 parts of sodium feldspar, 10 parts of calcined kaolin, 4 parts of barium carbonate, 4 parts of calcined zinc oxide, 4 parts of strontium carbonate, 10 parts of calcined talc, 12 parts of the first frit, 15 parts of the second frit, 3 parts of corundum (325 mesh), and 4 parts of wollastonite;

[0091] Example 12

[0092] The embodiment of the mirror surface low gloss non-prickly heat glaze and its preparation method and application described in the present invention is different from Example 1 only in that the raw materials for preparing the mirror surface low gloss non-prickly heat glaze include the following components in parts by weight: 20 parts of potassium feldspar, 14 parts of sodium feldspar, 10 parts of calcined kaolin, 3 parts of barium carbonate, 4 parts of calcined zinc oxide, 4 parts of strontium carbonate, 10 parts of calcined talc, 12 parts of the first frit, 17 parts of the second frit, 4 parts of corundum (325 mesh), and 3 parts of wollastonite;

[0093] Comparative Example 1

[0094] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0095] The raw materials for preparing the surface glaze layer include the following components in parts by weight: 15 parts of calcined kaolin, 22 parts of potassium feldspar, 15 parts of sodium feldspar, 6 parts of wollastonite, 2 parts of zinc oxide, 15 parts of quartz, 9 parts of aluminum oxide, 10 parts of nepheline, and 8 parts of zirconium silicate.

[0096] Comparative Example 2

[0097] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0098] The raw materials for preparing the surface glaze layer include the following components in parts by weight:

[0099] 23 parts of calcined kaolin, 6 parts of ball clay, 17.5 parts of potassium feldspar, 16 parts of sodium feldspar, 16 parts of quartz, 5 parts of calcined alumina, 14.5 parts of nepheline, and 2 parts of zinc oxide.

[0100] Comparative Example 3

[0101] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0102] The raw materials for preparing the surface glaze layer include the following components in parts by weight:

[0103] 10 parts of calcined kaolin, 20 parts of potassium feldspar, 15 parts of sodium feldspar, 12 parts of zirconium silicate, 10 parts of quartz, 3 parts of calcined alumina, 15 parts of the fourth frit, 10 parts of nepheline, 3 parts of barium carbonate, and 2 parts of burned talc.

[0104] Comparative Example 4

[0105] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0106] The raw materials for preparing the mirror surface low-gloss non-rash glaze include the following components in parts by weight:

[0107] 7 parts of potassium feldspar, 10 parts of sodium feldspar, 8 parts of calcined kaolin, 6 parts of barium carbonate, 3 parts of calcined zinc oxide, 9 parts of burned talc, 7 parts of the first frit, 18 parts of the second frit, 4 parts of zirconium silicate, 7 parts of nepheline, 15 parts of the fourth frit, and 6 parts of calcite.

[0108] Comparative Example 5

[0109] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0110] The raw materials for preparing the mirror surface low-gloss non-rash glaze include the following components in parts by weight:

[0111] 22 parts of potassium feldspar, 15 parts of sodium feldspar, 10 parts of calcined kaolin, 3 parts of barium carbonate, 3 parts of calcined zinc oxide, 4 parts of strontium carbonate, 4 parts of calcined talc, 8 parts of the first frit, 15 parts of the second frit, 3 parts of aluminum oxide, and 3 parts of wollastonite.

[0112] Comparative Example 6

[0113] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0114] The raw materials for preparing the mirror surface low-gloss non-rash glaze include the following components in parts by weight:

[0115] 12 parts of potassium feldspar, 20 parts of sodium feldspar, 12 parts of calcined kaolin, 3 parts of barium carbonate, 4 parts of calcined zinc oxide, 4 parts of strontium carbonate, 10 parts of calcined talc, 10 parts of the first frit, 18 parts of the second frit, 2 parts of corundum (325 mesh), and 7 parts of wollastonite.

[0116] Comparative Example 7

[0117] A mirror-finished low-gloss, non-prickly ash glaze and a preparation method and application thereof, which are different from Example 1 only in that the raw materials for preparing the mirror-finished low-gloss, non-prickly ash glaze include the following components in parts by weight: 20 parts of potassium feldspar, 20 parts of sodium feldspar, 13 parts of calcined kaolin, 3 parts of barium carbonate, 3 parts of calcined zinc oxide, 6 parts of strontium carbonate, 6 parts of burned talc, 17 parts of a second frit, 5 parts of aluminum oxide, and 7 parts of wollastonite.

[0118] Comparative Example 8

[0119] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0120] The raw materials for preparing the mirror surface low-gloss non-prickly heat glaze include the following components in parts by weight: 25 parts of potassium feldspar, 15 parts of sodium feldspar, 15 parts of calcined kaolin, 1 part of barium carbonate, 4 parts of calcined zinc oxide, 6 parts of strontium carbonate, 8 parts of calcined talc, 17 parts of the first frit, 5 parts of aluminum oxide, and 7 parts of wollastonite.

[0121] Comparative Example 9

[0122] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0123] The first molten block is replaced by a fifth molten block, and the fifth molten block includes the following chemical composition in percentage: Al2O39.49%, SiO258.56%, K2O8.03%, Na2O0.55%, CaO12.22%, MgO0.75%, and ZnO9.59%.

[0124] Comparative Example 10

[0125] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0126] The first sinter is replaced by a sixth sinter, which includes the following chemical compositions in percentage: Al2O3 19.19%, SiO2 61.41%, K2O 3.97%, Na2O 7.05%, CaO 6.93%, MgO 0.15%, and ZnO 1.01%.

[0127] Comparative Example 11

[0128] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0129] The second sinter is replaced by the seventh sinter, which includes the following chemical composition in percentage: Al2O3 18.59%, SiO2 54.03%, K2O 5.33%, Na2O 1.64%, CaO 8.55%, BaO 0.12%, ZnO 2.91%, MgO 2.19%, SrO 5.73%.

[0130] Comparative Example 12

[0131] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0132] The second sinter is replaced by the eighth sinter, which includes the following chemical composition in percentage: Al2O3 19.55%, SiO2 49.06%, K2O 8.32%, Na2O 3.72%, CaO 4.45%, BaO 0.24%, ZnO 4.92%, MgO 2.68%, SrO 6.64%.

[0133] Comparative Example 13

[0134] A mirror-like low-gloss non-rash glaze and a preparation method and application thereof, the difference from Example 1 is only that:

[0135] The ceramic tile is not provided with a protective glaze layer.

[0136] The chemical composition of the surface glaze layer in each embodiment and comparative example and the chemical composition of the mirror low-gloss non-prickly ash glaze are shown in Tables 1 and 2. It should be noted that, in addition to the chemical components described, Tables 1 and 2 also include very small amounts of other inevitable components (such as impurities or loss on ignition, etc.), which are not listed here one by one.

[0137] Table 1

[0138]

[0139] Table 2

[0140]

[0141]

[0142] Effect Example 2

[0143] In order to verify the various properties of the ceramic tile of the present invention, the ceramic tiles prepared in the embodiments and comparative examples were subjected to the following tests:

[0144] (1) Gloss test: WGG60-E4 photometer is used for testing in accordance with ISO-2767 and GB8941.2.

[0145] (2) Touch test: 10 testers were selected to touch each product and evaluate its touch (blindfolded). Pearls were used as a reference. Pearls have a delicate and smooth touch. The testers evaluated the touch of the products in comparison and gave scores. The closer the touch is to pearls, the higher the score. Conversely, the rougher or smoother the touch is, the lower the score. The scores were averaged. 9 to 10 points were excellent, 7 to 8 points were qualified, and below 7 points were unqualified.

[0146] (3) Appearance test: Confirm whether the surface of the tile is flat (with the mirror as a reference), observe whether there are defects such as orange peel, prickly heat, glaze shrinkage, etc., and whether the gloss of the surface is uniform.

[0147] (4) Wear resistance test: Tested according to GB / T4100-2015.

[0148] (5) Anti-slip test: Tested according to GB / T4100.3-1999 standard.

[0149] The test results are shown in Table 3.

[0150] Table 3

[0151]

[0152]

[0153]

[0154]

[0155] It can be seen from the results that the ceramic tile prepared by the mirror low-gloss non-prickly ash glaze of the present invention has ideal comprehensive properties, such as Figure 1 As shown, it not only has moderate glossiness, high appearance flatness, and no obvious appearance defects, especially no defects such as prickly heat and orange peel similar to existing products, but also has an ideal low-light mirror effect, and at the same time, the product has high wear resistance and anti-skid properties. The main reason is that after firing, the raw materials for preparing the mirror low-gloss prickly heat-free glaze of the present invention will not produce defects caused by crystallization or large height differences in refraction and reflection effects, and achieve a good appearance and low-light mirror effect. At the same time, the generated glass phase and microcrystals are evenly distributed, no microcracks are generated, and the arrangement density is high. Therefore, it not only has a delicate texture, but also has good anti-skid and wear resistance. Since the glaze has good light transmittance, there will be no uneven surface gloss when presenting printed patterns.

[0156] In contrast, although the mirror-like low-gloss non-prickly heat glazes described in Comparative Examples 4 to 6 use the same first and second frits, other raw materials are used improperly, which is similar to the existing product formula. Such a formula may cause the product to have obvious prickly heat or orange peel defects, poor flatness, low arrangement density of glass phase and microcrystalline grains, and easy to have microcracks. Therefore, the texture of the product is also poor, the hand feel is rough or greasy, and the anti-slip and wear resistance are poor. Figure 2 and 3As shown, the product of Comparative Example 4 has a high gloss, cannot achieve a mirror effect, and feels very greasy, while the product of Comparative Example 6 has an appearance defect similar to orange peel. The first and second frits are not introduced into the products of Comparative Examples 7 and 8, and effective columnar crystals cannot be precipitated, the glaze has low density, poor appearance and poor wear resistance; the frits used in the products of Comparative Examples 9 to 12 are not of the type specified by the present invention, and they also cannot achieve the ideal glaze effect, and the comprehensive performance of the products is poor, which fully illustrates that the raw materials for preparing the mirror low-gloss and flaky-free glaze in the products of the present invention, whether they are frits or other components, cannot achieve the ideal mirror low-gloss effect and use performance if the appropriate type is not selected. Further preferably, under appropriate ingredients, the formula and corresponding chemical composition of the raw materials for preparing the mirror low-gloss and flaky-free glaze used in Examples 1 to 10 are better than those in Examples 11 and 12, so the flatness is higher and the touch is more delicate and moist.

[0157] In addition, the ceramic tile product of the present invention also needs to use specific raw materials for preparation when constructing the glaze surface, so as to avoid excessive temperature difference between the glaze layer and the body layer during firing, thereby causing appearance defects and performance defects. As shown in Comparative Examples 1 to 3, the raw materials used for preparing the glaze layer are similar to those of conventional glaze products, wherein the amount of zinc and zirconium added to the material used in the product of Comparative Example 1 is relatively small, and no B2O3 is introduced. During the firing process, the product has obvious temperature differences between the layers, and the problem of untimely exhaust occurs. The product has obvious prickly heat defects, and the glossiness of the product is lower, such as Figure 4 As shown; the preparation raw materials introduced in the products of Comparative Examples 2 and 3 are different, and zinc oxide is not introduced, while Comparative Example 3 uses a large amount of barium source material. Obviously, the product cannot present an ideal light feeling, the gloss is low and the texture is rough, and the wear resistance and anti-slip performance are not ideal, especially the product of Comparative Example 3, such as Figure 5 As shown, the prickly heat defect of the product is very obvious.

[0158] According to the comparison between the products of Examples 1 to 3 and Examples 9 to 10, it can be seen that when the types of raw materials for preparing the glaze layer are the same, the products prepared according to the formula and chemical composition ratio described in Examples 1 to 3 are better in touch and smoothness.

[0159] In addition, the mirror low-gloss and anti-prickly glaze described in the present invention needs to be used together with a protective glaze when used, that is, a gradient layer needs to be constructed for the preparation raw materials of the mirror low-gloss and anti-prickly glaze. Otherwise, although the tile product has ideal gloss and wear resistance based on the mirror low-gloss and anti-prickly glaze, it will still have problems such as poor texture, appearance defects and poor anti-slip properties.

[0160] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A mirror-like low-gloss non-prickly heat glaze, characterized in that: The preparation comprises the following raw materials in parts by weight: 15-25 parts of potassium feldspar, 10-15 parts of sodium feldspar, 8-15 parts of calcined kaolin, 2-5 parts of barium carbonate, 3-6 parts of calcined zinc oxide, 3-5 parts of strontium carbonate, 5-10 parts of calcined talc, 10-18 parts of the first frit, 10-20 parts of the second frit, 2-4 parts of corundum, and 2-5 parts of wollastonite; The first frit includes the following chemical components in percentage by mass: Al2O3 16.58-18.94%, SiO2 56.34-60.65%, K2O 3.65-4.56%, Na2O 2.35-3.58%, CaO 15.62-17.50%, MgO 2.02-3.85%; The second frit includes the following chemical components in percentage by mass: Al2O3 18.58-20.94%, SiO2 49.34-55.15%, K2O 0.65-1.06%, Na2O 2.85-4.58%, CaO 8.62-10.50%, BaO 8.19-10.54%, ZnO 2.86-4.45%, and MgO 3.15-4.45%.

2. The mirror-like low-gloss non-prickly heat glaze according to claim 1, characterized in that: The mirror-surface low-gloss glaze without tarnish comprises the following chemical components in percentage by mass: Al2O3 18.10-20.12%, SiO2 49.94-58.51%, K2O 3.11-4.05%, Na2O 1.89-3.05%, CaO 4.12-6.68%, MgO 3.02-4.85%, ZnO 3.16-5.25%, BaO 4.19-6.54%, and SrO 2.01-3.

15.

3. A ceramic tile, characterized in that: Including the mirror-finished low-gloss, non-rash glaze as described in claim 1 or 2; The ceramic tile comprises a body, a surface glaze layer, an inkjet printing layer, a protective glaze layer and a mirror-like low-gloss non-prickly heat glaze which are stacked in sequence; The surface glaze layer comprises the following raw materials in parts by weight: 8-15 parts of calcined kaolin, 15-25 parts of potassium feldspar, 15-30 parts of sodium feldspar, 5-9 parts of wollastonite, 5-10 parts of a third frit, 3-5 parts of calcined zinc oxide, 5-10 parts of zirconium silicate, 5-12 parts of quartz, 7-12 parts of calcined aluminum oxide, and 5-10 parts of a fourth frit; The third frit includes the following chemical components in percentage by mass: Al2O3 17.65-19.45%, SiO2 52.24-56.68%, K2O 4.45-6.04%, Na2O 6.34-8.01%, CaO 8.12-12.18%, ZnO 1.01-2.45%; The fourth frit includes the following chemical components in mass percentage: Al2O3 10.14-15.12%, SiO2 50.14-55.68%, K2O 4.15-5.04%, Na2O 1.04-1.85%, CaO 8.12-10.18%, ZnO 4.01-5.45%, BaO 10.56-13.16%, and B2O3 1.98-3.54%.

4. The ceramic tile according to claim 3, characterized in that: The surface glaze layer includes the following mass percentages: Al2O3 20.12-25.56%, SiO2 52.14-59.14%, K2O 2.15-3.25%, Na2O2.85-4.51%, CaO 3.05-5.18%, B2O3 0.34-0.51%, MgO 0.22-1.05%, ZnO2.15-3.85%, BaO 0.39-1.24%, and ZrO2 4.54-7.65%.

5. The method for preparing a tile according to claim 3 or 4, characterized in that: The following steps are involved: (1) providing a body layer, and then polishing the body layer; (2) spraying water on the polished body layer to cool it down, and then providing a glaze layer on the body layer; (3) Printing a pattern on the glaze layer to form an inkjet printing layer; (4) providing a protective glaze layer on the inkjet printing layer; (5) applying a mirror-like low-gloss, non-rash glaze on the protective glaze layer to obtain a rough blank; (6) The rough blank is fired at 1180-1200° C., cooled, and edge-ground to obtain the ceramic tile.

6. The method for preparing a ceramic tile according to claim 5, characterized in that: The raw materials for preparing the protective glaze layer are the same as those for the mirror surface low-gloss non-prickly heat glaze.

7. The method for preparing a ceramic tile according to claim 6, characterized in that: The protective glaze layer is provided by electrostatically spraying a protective glaze slurry, wherein the protective glaze slurry comprises water and raw materials for preparing a mirror-like low-gloss non-prickly heat glaze, with a gram weight of 1.18 to 1.28 g / mL and an applied amount of 105 to 135 g / m 2 .

8. The method for preparing a ceramic tile according to claim 6, characterized in that: The mirror surface low gloss and no-prickly heat glaze is set by spraying the mirror surface low gloss and no-prickly heat glaze slurry, wherein the mirror surface low gloss and no-prickly heat glaze slurry comprises water and the preparation raw materials of the mirror surface low gloss and no-prickly heat glaze, and the gram weight is 1.88-1.92 g / mL, the spraying flow rate is 33-38 s / 100 mL, and the application amount is 410-450 g / m 2 .

9. The method for preparing a ceramic tile according to claim 5, characterized in that: The surface glaze layer is provided by spraying the surface glaze slurry, wherein the surface glaze slurry comprises water and the raw materials for preparing the surface glaze layer, and has a gram weight of 1.88-1.92 g / mL, a spraying flow rate of 33-38 s / 100 mL, and an applied amount of 410-450 g / m 2 .

10. The method for preparing ceramic tiles according to claim 5, characterized in that: The green body layer comprises the following raw materials in parts by weight: 12-20 parts of calcined kaolin, 20-25 parts of potassium sodium sand, 15-20 parts of ball clay, 5-10 parts of bentonite, 20-25 parts of potassium sodium water-ground powder, 3-8 parts of burned talc, and 2-5 parts of pyrophyllite.

Citation Information

Patent Citations

  • Magic star stone glazed brick with surface aventurine effect and preparation method thereof

    CN106673438A

  • Low-gloss transparent glaze, ceramic tile using low-gloss transparent glaze and preparation method of ceramic tile

    CN112707644A

  • Fabric texture matt glaze, matt frit, ceramic tile, application and preparation method

    CN113968675A

  • Antique glazed tile and preparation method thereof

    CN116177985A

  • Jade glaze ceramic plate, preparation method and application thereof, and composition for preparing jade glaze

    CN117185659A

Cited By

  • Polishing-free simulated stone ceramic tile and preparation method thereof

    CN120504496A